Importance of land use and rainfall in the dynamics of the Caatinga vegetation cover in Northeastern Brazil - Lucas Nunes de Araujo; Fernanda Kelly Gomes da Silva; Maria Betânia Ribeiro Gonçalves Medeiros; Dilma Maria de Brito Melo Trovão (Acta Scientiarum. Biological Sciences, 2023)
Many factors, such as climate, land use, and cultural and social aspects, influence the vegetation cover dynamics. We aimed to analyze the vegetation cover dynamics in three municipalities of the Brazilian semi-arid region (Aroeiras, Boqueirão, and Congo, state of Paraíba, Brazil) and to check for the influence of land use and inter-annual variations in rainfall. We selected 18 Landsat satellite images between 1995 and 2017. We performed supervised classification based on pre-established regions of interest: Closed or conserved vegetation, Sparse or disturbed vegetation, Exposed soil, Water bodies, clouds, and shadows, according to color, shape, and texture criteria. In addition, we collected data from the IBGE's Agricultural Census and annual rainfall. Variations in land use and rainfall variations worked synergistically on vegetation cover dynamics. In the municipality of Congo, very wet years were associated with higher percentages of closed vegetation and decreased soil exposure. High percentages of land use were related to a higher cover of sparse vegetation and exposed soil. In Boqueirão, we observed the opposite phenomenon, with drier years associated with higher percentages of closed vegetation and exposed soil. In Aroeiras, we identified no clear relationship between rainfall and variations in vegetation cover. Similar to that observed in the other municipalities, the abandonment of agricultural and cattle ranching activities increased dense vegetation. Our results show that the analysis of land use and vegetation cover dynamics in the semi-arid region represents a complex task ranging from regional factors, such as climate, characterized by inter-annual rainfall variations, to local factors, such as land use intensity and demographic/social aspects.